الوسائل البديلة في حل نزاعات عقود الاتحاد الدولي للمهندسين الاستشاريين: "في الأردن وفي سلطنة عمان" - العيسى,عبد الحنان محمد (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2019)
This research deals with the “Alternative Means in Resolving Disputes under the International Federation of Consulting Engineers in Jordan and Sultanate of Oman”. The defaults of construction projects in the countries under study which have been executed under a local model contract and derived from contracts issued by the International Federation of Consulting Engineers are due to technical and legal reasons. This study looks closely at problems and disputes which have arisen from the application of such provisions and reasons thereof. It also explains the effectiveness of the alternative means which have been used to settle such disputes. The researcher has relied on an inductive, analytical and comparative method. It highlights the important amendments in the Construction Contract (Red Book) and the issues that arose out of the application of these standard contracts. The important conclusions of the research are that the alternate dispute resolution is a preferable mode of dispute resolution in construction contracts and that the model FIDIC Construction Contract 1999 is a balanced contract which can be used internationally for all construction contracts. The problems which arose in execution of construction projects in the above mentioned countries are caused by conflicting laws and financial imbalance in construction contracts in addition to lack of technical, legal and professional capability. The researcher recommends that a unified Arabic Standard Contract for Construction projects should be devised at national level capability for management and execution of the construction contracts should be developed and the legislation on contracting and construction should be unified.